PELAKSANAAN GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA (Studi Kasus pada Desa Koto Kombu Kecamatan Hulu Kuantan Kabupaten Kuantan Singigi) - Ridho Alfajri; Nur Azlina; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Village finance is a strategic thing for the village as well as for the government above the village that is the important district of village finance in affirmed by the Law of Village Number 6 Year 2014 and PERMENDAGRI No. 113 Year 2014 on Village Financial Management. In the implementation and management of Village Finance should be managed on the basis of transparent, accountable, participatory principles and carried out in an orderly and disciplined budget. This is well realized in Koto Kombu Village where village finances are formulated by the village government of BPD and the community together. This research uses qualitative research method to get facts about financial management process in Koto Kombu village. The unit of analysis in this research is Koto Kombu Village Government. Data collection techniques used are in-depth interviews, observations and documentation to complete the data in this study. Koto Kombu Village has been participative involving the chairman of BPD and the community elements in the formulation of financial plans and village development. In the implementation and administration of the Village Koto Kombu based on PERMENDAGRI No.113 of 2014 on Village Financial Management so that the flow of implementation is good. Likewise in reporting and Accountability Koto Kombu Village Government has been transparent to the community related to the realization of village finances by disseminating financial statements to the elements of society.Keywords : Accountability, Village Financial Management, Village Government